Developing a SIoT compatible novel traffic simulator to evaluate and execute complex SIoT based algorithms in typical road traffic scenarios - Gazi, Sami Muhammad; Arko, Sayantan Roy; Gomes, Elizabeth Lina; Bin Shahid, Abrar (Brac University, 2022)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2021.